2010
DOI: 10.1016/j.combustflame.2009.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of reaction–diffusion effects on species mixing rates in turbulent premixed methane–air combustion

Abstract: The scalar mixing time scale, a key quantity in many turbulent combustion models, is investigated for reactive scalars in premixed combustion. Direct numerical simulations (DNS) of three-dimensional, turbulent Bunsen flames with reduced methane-air chemistry have been analyzed in the thin reaction zones regime. Previous conclusions from single step chemistry DNS studies are confirmed regarding the role of dilatation and turbulence-chemistry interactions on the progress variable dissipation rate. Compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…It was demonstrated in Ref. [43] based on three-dimensional detailed chemistry based DNS data that the SDR transport statistics for major species are qualitatively similar to that of SDR of reaction progress variable c obtained from simple chemistry DNS data. The reaction progress variable c is defined based on a suitable reactant mass fraction in the following manner:…”
Section: Numerical Implementationmentioning
confidence: 53%
See 1 more Smart Citation
“…It was demonstrated in Ref. [43] based on three-dimensional detailed chemistry based DNS data that the SDR transport statistics for major species are qualitatively similar to that of SDR of reaction progress variable c obtained from simple chemistry DNS data. The reaction progress variable c is defined based on a suitable reactant mass fraction in the following manner:…”
Section: Numerical Implementationmentioning
confidence: 53%
“…Thus, the dynamic formulation based on the LES-G model seems to be a viable option for algebraicÑ c closure for turbulent premixed combustion. However, this newly proposed model has been assessed here based on simple chemistry DNS for moderate values of Re t with decaying turbulence and thus needs to be assessed further based on detailed chemistry based DNS data for higher values of Re t despite a previous analysis [43] demonstrated that the SDR statistics obtained from detailed chemistry DNS remain qualitatively similar to the conclusions drawn from simple chemistry DNS. Although the static version of the LES-G model has already been implemented in actual LES simulations and satisfactory agreement with experimental findings has been obtained [8,41], the proposed dynamic model also needs to be implemented in actual LES simulations in a configuration for which experimental data is available for the purpose of aposteriori assessment.…”
Section: Discussionmentioning
confidence: 95%
“…The simulation configuration involves a slot-jet turbulent Bunsen flame that is periodic in the span-wise z-direction (the coordinate system is indicated in Figure 1). Four cases (C1, C2, C4, C5) are considered that all have a mean equivalence ratio equal to 0.7, but different equivalence ratio stratification: C1, a perfectly-premixed Bunsen flame with equivalence ratio 0.7 reported in previous studies [10,11,12]; C2, a tangentially-stratified Bunsen flame configuration shown in Figure 1 The fuel-air mixture fraction , which equals zero in pure air and unity in pure methane, is linearly related to the case mixture fraction Z.…”
Section: Introductionmentioning
confidence: 99%
“…These situations are schematically shown in Figure 1, and this change is because of the fact that the dilatation due to heat release is strong compared to the turbulent strain rate. Evidence for such a behaviour has been found in direct numerical simulation (DNS) studies of statistically planar [16][17][18][19][20]22], spherically symmetric [25], and Bunsen [26] flames and also experimental bluff body stabilised flames [27]. As a consequence, the isoscalar surfaces are brought together by the compressive strain resulting in an increase of scalar gradient when the reaction is passive.…”
Section: Physics Of Reactive Scalar Mixingmentioning
confidence: 91%